plz solve

Asked by  | 6th Jun, 2008, 07:21: PM

Expert Answer:

sin-1 (1-x) - 2 sin-1x  = /2

sin-1 (1-x) - 2 sin-1x  =  sin-1 (1-x)  +  cos-1 (1-x) 

                                     (  sin-1x  +  cos-1x  = /2)

 - 2 sin-1x  =  cos-1 (1-x)

Now,let  sin-1x = a,then  -2a = cos-1 (1-x)

  or        cos2a =  1 - x               cos(-x) = cosx 

        1 - 2 sin2a = 1 - x            1 - 2x= 1 - x   

                                                                         (  sin a = x )

    2x- x = 0           x = 0 , 1/2

      x = 1/2 is avoided, as it is not true.

    x = 0 is the only solution.                      

Answered by  | 7th Jun, 2008, 08:43: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.